Analisis Kinerja Bangunan Gedung Tinggi Dengan Penambahan Dinding Geser (Studi Kasus: Bangunan 8 Lantai) - M Mirza Abdillah Pratama; Septiana Dyah Sugmana Putri; Edi Santoso (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2021)
Shear walls in high-rise buildings serve to increase the resistance of high-rise buildings to lateral loads. This study aims to compare the structural performance of an existing 8 (eight) storey building designed as a special moment resisting frame structure against a building designed as a dual system, which consists of: structural vibration time, base shear force, displacement, and drift. Three configurations for shear walls are designed, as follows: (1) L-shaped located at the corner of one side of the building, totaling 2 (two) units (SW1); (2) L-shaped located at the four corners of the building totaling 4 (four) units (SW2); and 3) I-shaped located along the side of the building totaling 6 (six) units (SW3). Simulations are run using the Etabs by taking into account dead loads, live loads, and earthquake loads. The results show that the addition of shear walls can: (1) reduce the vibration period of the structure up to 62,55% in SW3, (2) increase the base shear force up to 86,34% in SW3, (3) reduce peak displacement up to 84,86% in SW3, and (4) reduce the drift between floors up to 89,58% in SW3. However, the SW2 is considered to be better applied to the building by taking into account the structural performance, effectiveness and efficiency factors.